Domar, expectations, and growth stabilization - Mauro Boianovsky (Duke University, Center for the History of Political Economy (CHOPE), 2020)
Evsey Domar put forward in a couple of articles in the 1940s a "guaranteed income growth proposal." For the first time in macroeconomics, economic policy was supposed to work merely through the impact of its announcement on expectations. He claimed that optimistic expectations of income growth would be created by credible announcement to use government spending to bring the economy to its required growth rate. Confident expectations generated by government's assurance of future growth would induce private investment decisions in a scale that would bring about the required growth rate and by that justify the expectations, without putting the guarantee to test. This paper presents a detailed treatment of Domar's stabilization plan in the context of his growth model, together with discussion of similar ideas put forward by Roy Harrod and of critical reactions by Alvin Hansen.
Keywords: B22; B31; E61; 330; Domar; expectations; guaranteed growth; stabilization policy